Bioorthogonal Conjugation Directed by a Sugar‐Sorting Pathway for Continual Tracking of Stressed Organelles. (4th July 2018) - Xue, Zhongwei; Zhang, Enkang; Liu, Jian; Han, Jiahuai; Han, Shoufa
Abstract: Selective and continuous tracking of dynamic organelles is crucial for modern biology. We herein report a ship‐in‐a‐bottle strategy for tagging lysosomes by a strain‐promoted azide–alkyne cycloaddition to couple a pH sensor (RC) with mannose‐6‐carboxylate (M6C) actively transported into lysosomes through cell sorting. In contrast to classical acidotropic sensors, which are prone to dissipate from lysosomes, M6C‐RC formed in situ is stably trapped in lysosomes without resort to lysosomal acidity and exhibits "always‐on" blue fluorescence to pinpoint lysosomes and red‐to‐blue fluorescence ratios indicative of the lysosomal pH value. These advantages enable tracking of stressed lysosomes, and necrosis to be differentiated from apoptosis on the basis of lysosomal pH changes. The cell‐sorting‐mediated bioorthogonal tagging strategy offers a new route to track stressed organelles with disrupted physiological organelle–probe affinity.